Action of neem oil (Azadirachta indica A. Juss) on cocoon spinning in Ceraeochrysa claveri (Neuroptera: Chrysopidae) - Scudeler, Elton Luiz [UNESP]; Garcia, Ana Silvia Gimenes [UNESP]; Padovani, Carlos Roberto [UNESP]; Santos, Daniela Carvalho [UNESP] (Elsevier, 2013)
Neem oil is a biopesticide that disturbs the endocrine and neuroendocrine systems of pests and may interfere with molting, metamorphosis and cocoon spinning. The cocoon serves protective functions for the pupa during metamorphosis, and these functions are dependent on cocoon structure. To assess the changes in cocoon spinning caused by neem oil ingestion, Ceraeochrysa claveri larvae, a common polyphagous predator, were fed with neem oil throughout the larval period. When treated with neem oil, changes were observed on the outer and inner surfaces of the C. claveri cocoon, such as decreased wall thickness and impaired ability to attach to a substrate. These negative effects may reduce the effectiveness of the mechanical and protective functions of cocoons during pupation, which makes the specimen more vulnerable to natural enemies and environmental factors. © 2013 Elsevier Inc.
Keywords: Biopesticide; Cocoon; Lacewing; Nonwoven; Ultrastructure